The Influence of Country of Origin, Perceived Product Quality And Social Media Marketing on Consumers Purchase Decision at E-Marketplace Lazada With Purchase Interest as Intervening - Dharmawan, Jovita; Sanjaya, Ridwan (Soegijapranata Catholic University, 2024)
The aim of this research is to analyze the influence of country of origin, social media marketing, product quality perceptions, Consumer interest in visiting Lazada influences consumer decisions to make purchases at Lazada with consumer purchase interest as an intervening variable. The object of this research is consumers' decisions to make purchases at Lazada. The population in this research is all Lazada consumers. The sampling method is purposive sampling taken using Google Form. The total number of respondents in this research was 173 Lazada consumer respondents. The analysis used in the research is structural equation modeling. The results of this research are that country of origin, social media marketing and perceived product quality have a positive and significant effect on consumer interest in visiting Lazada. Social media marketing, perceived product quality, consumer interest in visiting Lazada have a positive influence on consumer decisions to make purchases at Lazada. Country of origin does not have a significant effect on consumers' decisions to make purchases at Lazada. Consumer interest in visiting Lazada intervenes in the influence of country of origin, social media marketing and perceptions of product quality on consumer decisions to purchase at Lazada.